Body Composition of Chronic Kidney Disease Patients: A Multi-Stage Analysis (Journal of Renal and Hepatic Disorders, 2021)
With accelerated muscle proteolysis, a decrease in muscle mass is evident in chronic kidney disease (CKD) patients. This eventually leads to nutritional disturbance that for a long has been mostly attributed to malnutrition. This predisposes patients to premature morbidity and mortality. Assessing body composition, thus, becomes vital. In this cross-sectional study, CKD patients (n = 47) of stages 2, 3a, 3b and 4 were assessed for their lean tissue mass, adipose tissue mass and overhydration by body composition monitor. Lean tissue index and fat tissue index were calculated as lean tissue mass and adipose tissue mass in kilogram divided by patients’ height in square meters. Patients were assessed for their handgrip strength (HGS) by Jamar hydraulic hand dynamometer, and also for their 7-day diet history. Mean lean tissue index of CKD patients was 11.73 ± 2.49 kg/m2. About 34 (72.3%) out of 47 patients were below the reference value of lean tissue index. A significant difference in lean tissue index (P = 0.03) was observed at various stages. Patients at stage 4 had the lowest lean tissue index. Lean tissue was significantly (P = 0.03) low in patients consuming protein
Keywords: body composition; chronic kidney disease; lean tissue index; malnutrition; muscle strength